Myths of mighty women : their application in psychoanalytic psychotherapy - Richards, Arlene; Spira, Lucille (Psychoanalysis & women series., 2015)
Women whose mothers were not called upon to achieve in a man's world have a difficult time seeing themselves as powerful enough to do that. Identifying with mighty women of the past and of the present culture can help them to permit themselves to achieve more than their mothers did. This book provides several such myths from ancient and modern cultures, from both Western and Eastern traditions, each of which is a standard for a particular aspect of female power and all of which can provide that power for women now. Among the aspects of women's power are Super Girl, Warrior Woman, Evil Temptres.